Advances in Understanding the Karyotype Evolution of Tetrapulmonata and Two Other Arachnid Taxa, Ricinulei and Solifugae - Král, Jiří; Sember, Alexandr; Divišová, Klára; Kořínková, Tereza; Reyes Lerma, Azucena C; Ávila Herrera, Ivalú M; Forman, Martin; Šťáhlavský, František; Musilová, Jana; Torres Kalme, Sabrina; Palacios Vargas, José G; Zrzavá, Magda; et al. (Genes, 2025)
BACKGROUND/OBJECTIVES: Arachnids are a megadiverse arthropod group. The present study investigated the chromosomes of pedipalpid tetrapulmonates (orders Amblypygi, Thelyphonida, Schizomida) and two arachnid orders of uncertain phylogenetic placement, Ricinulei and Solifugae, to reconstruct their karyotype evolution. Except for amblypygids, the cytogenetics of these arachnid orders was almost unknown prior to the present study. METHODS: Chromosomes were investigated using methods of standard (Giemsa-stained preparations, banding techniques) and molecular cytogenetics (fluorescence in situ hybridization, comparative genomic hybridization). RESULTS AND CONCLUSIONS: New data for 38 species, combined with previously published data, suggest that ancestral arachnids possessed low to moderate 2n (22-40), monocentric chromosomes, one nucleolus organizer region (NOR), low levels of heterochromatin and recombinations, and no or homomorphic sex chromosomes. Karyotypes of Pedipalpi and Solifugae diversified via centric fusions, pericentric inversions, and changes in the pattern of NORs and, in solifuges, also through tandem fusions. Some solifuges display an enormous amount of constitutive heterochromatin and high NOR number. It is hypothesized that the common ancestor of amblypygids, thelyphonids, and spiders exhibited a homomorphic XY system, and that telomeric heterochromatin and NORs were involved in the evolution of amblypygid sex chromosomes. The new findings support the Cephalosomata clade (acariforms, palpigrades, and solifuges). Hypotheses concerning the origin of acariform holocentric chromosomes are presented. Unlike current phylogenetic hypotheses, the results suggest a sister relationship between Schizomida and a clade comprising other tetrapulmonates as well as a polyploidization in the common ancestor of the clade comprising Araneae, Amblypygi, and Thelyphonida.
Keywords: molekulární evoluce; nucleolus organizer region; holocentric; sex chromosome; hybridizace in situ fluorescenční; solifuge; spider; karyotyp; karyotypizace; Evolution, Molecular; heterochromatin; Karyotype; Karyotyping; In Situ Hybridization, Fluorescence; telomere; pavoukovci; zvířata; fylogeneze; polyploidy; Ricinulei; somatic pairing; Phylogeny; Arachnida; Animals